2018
DOI: 10.22434/ifamr2016.0162
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of certification of independent oil palm smallholders in Indonesia

Abstract: Sustainable certification schemes have surged in recent years. The introduction of these schemes poses serious challenges to smallholders. One such certification scheme is the Roundtable on Sustainable Palm Oil (RSPO), which uses certification to increase equitable and sustainable production of palm oil. This study calculates upfront and recurrent costs and monetary benefits of RSPO certification for the Amanah Independent Oil Palm Smallholders Association in Ukui District, Indonesia. Survey and interview data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 16 publications
2
45
0
4
Order By: Relevance
“…Despite the responses in vegetative growth and bunch weight that we observed, the costs of the additional nutrient applications far outweighed the benefits, even without considering the additional labour investments for fertiliser application. These results are in line with the findings of Hutabarat et al (2018), who studied a group of RSPO-certified independent smallholders and observed that the implementation of better management practices similar to ours, in combination with RSPO certification, led to a small increase in yield but a decrease in farm income, due to the great increase in costs. It is likely that fertiliser application and other BMPs will have a stronger effect on yield in plantations which are more nutrient-constrained and have poorer starting yields.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Despite the responses in vegetative growth and bunch weight that we observed, the costs of the additional nutrient applications far outweighed the benefits, even without considering the additional labour investments for fertiliser application. These results are in line with the findings of Hutabarat et al (2018), who studied a group of RSPO-certified independent smallholders and observed that the implementation of better management practices similar to ours, in combination with RSPO certification, led to a small increase in yield but a decrease in farm income, due to the great increase in costs. It is likely that fertiliser application and other BMPs will have a stronger effect on yield in plantations which are more nutrient-constrained and have poorer starting yields.…”
Section: Discussionsupporting
confidence: 92%
“…In Jambi in particular, the participants rigorously followed the recommended 10-day harvesting round in the period 2014-2016 (both in the BMP and in the control plots) but stopped doing so in 2017 because of personal circumstances of the lead farmer, who was also the trader. Increased harvesting frequency has been proposed as a strong driver of increased bunch yield (Donough et al, 2010;Lee et al, 2013) and improved oil content and quality (Corley, 2001;Donough, 2003), leading to improved bunch prices (Hutabarat et al, 2018). The combination of better harvesting practices and better drainage could explain a large part of the excellent 2015 yields in Jambi, and the return to a 15-day harvesting interval combined with flooding in 2017 may explain why yields were reduced in that year.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smallholders need additional costs to meet the standards while additional yield and revenue might be uncertain (Hutabarat, Slingerland, Rietberg, et al, 2017).…”
Section: Certification Is a Documented Agreementsmentioning
confidence: 99%